Kecenderungan penggunaan paylater di kalangan mahasiswa: Peran perilaku konsumtif dan tekanan sosial - Candika, Yossy Imam; Riadi, Faicha Sintya; Putri, Eka Lestari Hafqi; Bahtera, Novyandri Taufik (Journal of Management and Digital Business, 2025)
The use of PayLater services among university students has increased significantly, particularly in major cities like Surabaya. This phenomenon is influenced by a growing consumptive lifestyle and social pressure from the surrounding environment. This study aims to analyze the influence of consumptive behavior and social influence on the decision to use PayLater services among students in Surabaya. The research was conducted in May 2024 using a quantitative method with a survey approach. Primary data were collected from 75 university students in Surabaya who have used PayLater services, and analyzed using multiple linear regression. The results show that consumptive behavior has a significant influence on the decision to use PayLater, while social influence is positive but not statistically significant. These findings indicate that student decisions are more strongly driven by a consumptive lifestyle than by social pressure. Therefore, PayLater service providers are advised to design marketing strategies aligned with students’ consumption patterns. Additionally, educational institutions and financial regulators should enhance financial literacy education to mitigate irresponsible use of PayLater services that may impact students’ future financial well-being.